Genome-wide analysis of long noncoding RNA expression profile in nasal mucosa with allergic rhinitis - Xian Wei; Man Xu; Chao Wang; Shengjian Fang; Yu Zhang; Weihua Wang (BMC, 2021)
Abstract Background Long noncoding RNAs (lncRNAs) are involved in a variety of human immune diseases. However, the expression profile and precise function of lncRNAs in allergic rhinitis (AR) remain unknown. In the present study, genome-wide analysis of lncRNA expression was performed in the nasal mucosa tissue and mRNA regulatory relationship was examined among patients with or without AR. Methods Microarray assays were performed and the differential expressions of lncRNAs or mRNA were verified through RT-PCR. The lncRNA functions were annotated using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). The potential regulatory relationships between lncRNAs and the co-expressed mRNAs were analyzed using Cytoscape software. The expressions of specific lncRNAs and mRNAs were examined using an in vitro cell model. Results A total of 57 lncRNAs and 127 mRNAs were dysregulated in the nasal mucosa tissue of patients with AR, compared to those of patients without AR (fold change > 2.0 and P < 0.05). GO and pathway analysis indicated that the lncRNA-co-expressed mRNAs were enriched in several biological processes and cellular signaling pathways related to AR, such as positive regulation of the integrin biosynthetic process, cell adhesion, and leukocyte transendothelial migration. Some lncRNAs regulated the co-expressed genes in a cis- and/or trans-regulatory manner. Furthermore, allergen exposure significantly increased the expression of lnc-CXCL12-4, CXCL12, and CXCR4 in BEAS-2B cells compared to untreated cells (P < 0.01). Conclusion The results of the present study suggest that lncRNAs participate in the biological pathways related to AR. Leukocyte transepithelial migration may be a potential target for lncRNAs to regulate allergic inflammation and CXCL12/CXCR4 axis plays an important role in the inflammatory process of AR.